Shedding of glycan‐modifying enzymes by signal peptide peptidase‐like 3 (SPPL3) regulates cellular N‐glycosylation. (29th October 2014) - Voss, Matthias; Künzel, Ulrike; Higel, Fabian; Kuhn, Peer‐Hendrik; Colombo, Alessio; Fukumori, Akio; Haug‐Kröper, Martina; Klier, Bärbel; Grammer, Gudula; Seidl, Andreas; Schröder, Bernd; Obst, Reinhard; et al.
Abstract Protein N‐glycosylation is involved in a variety of physiological and pathophysiological processes such as autoimmunity, tumour progression and metastasis. Signal peptide peptidase‐like 3 (SPPL3) is an intramembrane‐cleaving aspartyl protease of the GxGD type. Its physiological function, however, has remained enigmatic, since presently no physiological substrates have been identified. We demonstrate that SPPL3 alters the pattern of cellular N‐glycosylation by triggering the proteolytic release of active site‐containing ectodomains of glycosidases and glycosyltransferases such as N‐acetylglucosaminyltransferase V, β‐1, 3 N‐acetylglucosaminyltransferase 1 and β‐1, 4 galactosyltransferase 1. Cleavage of these enzymes leads to a reduction in their cellular activity. In line with that, reduced expression of SPPL3 results in a hyperglycosylation phenotype, whereas elevated SPPL3 expression causes hypoglycosylation. Thus, SPPL3 plays a central role in an evolutionary highly conserved post‐translational process in eukaryotes.